PRESPEKTIF AYAT AL-QUR’AN DALAM ETIKA BISNIS ISLAM KONTEMPORER - Nabbila, Faricha Lita; Syakur, Ahmad (Pusat Riset dan Inovasi Nasional, 2023)
Business with everything that happens in people's lives every day in general. The large number of businesses and the variety of business motives and orientations as well as the increasing complexity of business problems, sometimes makes business people fixated on trying anything to achieve their goals, especially if the goal is only to seek profit and profit. So that negative actions often occur, which eventually become habits in business behavior. If so, it is not uncommon for business actors to be identified with dirty deeds, because there are behaviors such as lying, betrayal, breaking promises, deceiving and defrauding others. This article describes business in an Islamic approach which includes Islamic business concepts, Islamic business principles and normative foundations of Islamic business by using a review of literature studies by examining interpretations of the Qur'an regarding the relationship between verses and existing ethical rules. Islamic business must be based on Islamic ethics which originate from the Al-Qur'an and the Sunnah of the Prophet Muhammad SAW. Generally, business ethics is a normative discipline, whereby certain ethical standards are formulated and then applied. It makes specific judgments about what is right or wrong, that is to say, makes claims about what to do or what not to do.